2020
DOI: 10.3322/caac.21650
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA in advanced solid tumors: Clinical relevance and future directions

Abstract: The application of genomic profiling assays using plasma circulating tumor DNA (ctDNA) is rapidly evolving in the management of patients with advanced solid tumors. Diverse plasma ctDNA technologies in both commercial and academic laboratories are in routine or emerging use. The increasing integration of such testing to inform treatment decision making by oncology clinicians has complexities and challenges but holds significant potential to substantially improve patient outcomes. In this review, the authors di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 150 publications
(207 reference statements)
0
99
0
Order By: Relevance
“…It’s groundbreaking that, not like any other conventional factors for recurrence risk stratification (high versus low), detection of ctDNA is the reflection of MRD itself (yes versus no). As the ctDNA measuring technology continues to evolve and manifest its significance [ 19 ], the real-time detection of MRD using ctDNA may help guide the precise administration of ACT, evaluation of ACT efficacy, and monitoring of disease recurrence. The potential paradigm-changing clinical applications of this ctDNA-guided strategy can be summarized as follows.…”
Section: Discussionmentioning
confidence: 99%
“…It’s groundbreaking that, not like any other conventional factors for recurrence risk stratification (high versus low), detection of ctDNA is the reflection of MRD itself (yes versus no). As the ctDNA measuring technology continues to evolve and manifest its significance [ 19 ], the real-time detection of MRD using ctDNA may help guide the precise administration of ACT, evaluation of ACT efficacy, and monitoring of disease recurrence. The potential paradigm-changing clinical applications of this ctDNA-guided strategy can be summarized as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported associations between each somatic mutation and the clinicopathological characteristics of EC [8] , [9] , [10] , few studies have focused on a comprehensive somatic mutation analysis [6] . More recently, plasma circulating tumor DNA (ctDNA) has been reported to be effective in early diagnosis and therapeutic monitoring in human cancers [11] . As blood samples are easy to obtain multiple times on demand in a non-invasive method compared with standard tumor biopsy, somatic mutations become increasingly important as clinically useful biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Therapies at baseline in advanced NSCLC rely on many different factors ( Figure 2 ). A LB at diagnosis in late stage NSCLC was initially performed to detect genomic alterations in EGFR [ 20 , 21 , 34 , 35 ]. Notably activating EGFR mutations can be detected in LB from NSCLC, which is now performed in the daily practice of many clinical centers [ 36 , 37 , 38 ].…”
Section: Ngs With Blood Samples At Diagnosis Of Advanced Non-small Cell Lung Carcinomamentioning
confidence: 99%